A FINANCING EU MILITARY OPERATIONS: THE ATHENA MECHANISM - Chevleski, Aleksandar; Gligorova, Anita (International Scientific Journal Vision, 2018)
On 23 February 2004, the Council adopted Decision 2004/197/CFSP establishing a mechanism to administer the financing of the common costs of Union operations having military or defence implications. The Decision was amended by the Council Decision 2011/871/CFSP, and more recently, in 2015 the Council adopted a new Decision regarding the ATHENA mechanism. The structure for fi nancing EU external action is fl exible and fragmented: CSDP operations are not entirely budgetized; the administrative costs for the CSDP institutional framework are borne by the CFSP budget, but the operational costs for the diff erent CSDP missions/operations are borne by diff erent mechanisms. Operations having military and defence implications are fi nanced directly by the participating Member States and particularly via the specifi c mechanism – ATHENA. Such fragmentation does not provide for coherence of EU external action nor continuous/stable fi nancing of EU military operations. Mostly, Athena fi nances the costs incurred for the headquarters, some types of infrastructure works, medical services, satellite imagery, transport to and from the theatre of operations for deployment. The 2018 saw a signifi cant ambition to overcome the problems of fi nancing the common costs via the establishment of the European Peace Facility (EPF) which will replace and supersede the Athena mechanism and the APF and will signifi cantly broaden the percentage of the costs covered for a wide range of CSDP operations/missions. The proposal for establishing an EPF is currently under discussion.